Machaut's Monophonic Virelai Tuit mi penser: Intersections of Language Sound, Pitch Space, Performance, and Meaning. - Latartara, John (Journal of Musicological Research)
While analyses of vocal music often highlight connections between textual meaning and musical structure, less common is the study of language sounds in relation to musical structure. An exploration of Guillaume de Machaut's monophonic virelai Tuit mi penser highlights connections that exist between language sounds, pitch space, performance, and meaning. In particular, the refrain of Tuit mi penser fuses the pitch motion with the language sound progression to create a darkening trajectory of the musical sound. This musical sound progression is seen both in Machaut's notation as well as two performances using spectrographs, which are computer images of musical performance. A comparison of Machaut's notation with sonic analysis of actual musical performances reveals the intersections between not only pitch, language sound, and performance, but also musical structure and semantic meaning of the text.